PERENCANAAN GEDUNG 5 LANTAI PONDOK PESANTREN DARUSSALAM SUMBERSARI DESA KENCONG KECAMATAN KEPUNG KABUPATEN KEDIRI - mu’minin, Amirul; Umam, Khotibul; Rochmanto, Decky; Khitam, Akhmad Firdos Khoiril; Amirotul Husna, Diana; Dinda Afnika, Naufa; Habib Sholahuddin, Moch. (SAINTIS Jurnal ilmu-ilmu eksakta, 2025)
Darussalam Islamic boarding school is an educational institution based on Islamic boarding schools with integrated learning methods. The many levels of education from MI-MA, resulting in an increase in the number of students each year, this makes the capacity of the Darussalam Islamic boarding school building inadequate. Based on this, development needs to be carried out to be able to meet the capacity of these students and female students. In the planning for the construction of the boarding school, it is planned to be 5 floors high using the reference of SNI 2847-2019 with a design concrete quality (fc’) of 30 MPa and a steel quality (fy) of 240 MPa and 420 MPa. Based on this, the planning results were obtained as follows: floor slab used 12–250 reinforcement and roof plate 10–250 (2) main beam for support area used 3-D16 top reinforcement, 2-D16 bottom reinforcement; the stirrup reinforcement used in the beam structure in the support area is D10-100 and the field area is D10-150; for practical beam support area used top reinforcement 2-D19, bottom reinforcement 2-D19; the stirrup reinforcement used in the structural beam structure in the support area is D10-100 and the field area is D10-150 (3) practical column for the main reinforcement is used D22 and the stirrup reinforcement is used D10-100; Practical column for main reinforcement is used D19 and stirrup reinforcement is used D10-100 (4) piles for main reinforcement are used 7-D13 mm, and stirrup reinforcement is spiral 10–150 mm.